2017
DOI: 10.5194/isprs-annals-iv-2-w4-157-2017
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Machine Learning Methods for Separating Wood And Leaf Points From Terrestrial Laser Scanning Data

Abstract: ABSTRACT:Classification of wood and leaf components of trees is an essential prerequisite for deriving vital tree attributes, such as wood mass, leaf area index (LAI) and woody-to-total area. Laser scanning emerges to be a promising solution for such a request. Intensity based approaches are widely proposed, as different components of a tree can feature discriminatory optical properties at the operating wavelengths of a sensor system. For geometry based methods, machine learning algorithms are often used to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 31 publications
1
58
1
Order By: Relevance
“…1) Random Forest: One of the main reasons for choosing RF for building the leaf-wood classification model is that RF is robust to outliers, and hence avoids overfitting by building multiple parallel decision trees using random subsets of data and random subsets of features for each tree [35]. A recent study has shown that RF outperformed other individual machine-learning classifiers like Naive Bayes, neural networks, and so on, for leaf and wood classification of individual trees based on geometric features in temperate forests [11]. To choose the optimal number of decision trees to build the model, we analyzed the performance of the models built with 10-80 decision trees by cross-validation.…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…1) Random Forest: One of the main reasons for choosing RF for building the leaf-wood classification model is that RF is robust to outliers, and hence avoids overfitting by building multiple parallel decision trees using random subsets of data and random subsets of features for each tree [35]. A recent study has shown that RF outperformed other individual machine-learning classifiers like Naive Bayes, neural networks, and so on, for leaf and wood classification of individual trees based on geometric features in temperate forests [11]. To choose the optimal number of decision trees to build the model, we analyzed the performance of the models built with 10-80 decision trees by cross-validation.…”
Section: Model Developmentmentioning
confidence: 99%
“…In the past decade, there have been significant advancements in the methods for leaf and wood separation from TLS data. The methods developed were either based on the radiometric features [10] or geometric features [8], [11]- [16] or a combination of both [17]. Since the radiometric features mainly depend on the wavelength used by a particular sensor, methods based on radiometric features become sensorspecific.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The drawback is that they require laborious and time consuming manual selection of training data. In addition, the distribution of training data greatly impacts the overall performance of machine learning methods (Wang, Hollaus, & Pfeifer, 2017). A combination of geometric and radiometric features may have advantage over using only one type (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%